The influence of water loss by evaporation in the tensile adhesion strength between dry-set mortar and ceramic tiles - Póvoas, Yêda Vieira (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Open time is one of the main characteristics of dry-set mortars. Water loss by both evaporation and suction is an important factor that influences its performance, since it may cause an adhesion failure after short ageing. It was determined that open time has a tensile adhesion strength of 0,5 MPa. This research aims to study the influence of water loss by evaporation in the tensile adhesion strength between dry-set mortar and ceramic tile. A test of tensile adhesion strength is performed, considering different intervals of time of the ceramic tile application on the mortar, according to a procedure that eliminates water loss by suction. The mortar is spread onto a glass plate, avoiding water loss by suction. After specified intervals of time for the application of ceramic tile according to the open time test, the system is cured for 28 days at 23 ºC and 65% relative humidity. After being cured, the dry-set mortar/ceramic tile system is glued onto the concrete slab by the surface previously in contact with the glass, for later pull-out. The tension and form of rupture are observed. The results show the effect of water loss by evaporation on the tensile adhesion strength, and the analysis indicates that a simple test of water loss by evaporation can determine the tensile adhesion strength of the dry-set mortar.